Assessing amino acid solubility of black soldier fly larvae meal in Atlantic salmon (Salmo salar) in vivo and in vitro - Radhakrishnan, Gopika; Silva, Marta S.; Lock, Erik-Jan; Belghit, Ikram; Philip, Antony Jesu Prabhu (Frontiers in Physiology, 2022)
In vitro and in vivo methods were used to evaluate amino acids solubility of black soldier fly (BSF) larvae meal and two experimental diets (reference and test diets) for Atlantic salmon. The current study used in vitro method such as pH stat to compare and standardise the salmon extracted enzyme (SE), and commercial enzyme (CE) based on their hydrolytic capacity on a purified protein substrate. Further, an in vitro amino acid solubility of feed ingredients and diets were measured using the standardised enzyme volume from SE and CE. Results showed that SE and CE exhibit similar protein hydrolytic capacity upon standardisation on purified substrates. However, when using the two-stage hydrolysis (acidic and alkaline steps), significantly higher amino acid solubility was observed with CE except for glycine, and proline which were equally solubilised by both SE, and CE. No significant difference was observed between reference and test diet using the SE except for tyrosine, valine, leucine, and phenylalanine, which were significantly higher solubilised in reference diet than test diet. Whereas higher solubility of valine, isoleucine, aspartic acid, and glutamic acid was observed in test diet using CE than SE. Similarly, the solubility of valine, isoleucine, and glutamic acid were higher in BSF larvae meal when CE was used. The in vivo true protein digestibility of BSF larvae meal was 99%, and 81% for the test diet containing BSF larvae meal. The results demonstrated a positive correlation (r = 0.91; p < 0.01) between salmon and commercial enzymes but overall, no significant correlation was observed for amino acid solubility between in vivo and in vitro . However, there was a strong positive correlation for protein solubility using SE (r = 0.98) than CE (r = 0.74) with the in vivo true protein digestibility. The efficiency of SE, and CE can be compared, and standardised based on DH%, and hence correlates better with the in vivo protein digestibility but not with amino acid solubilities.